PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - Luh Putu Ersamiya Ika Jayanthi; I Ketut Putu Suniantara (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to examine the influence of organizational culture on employee performance through job satisfaction at the STIKOM Bali Institute of Technology and Business (ITB). In this research, researchers used 102 respondents as samples using the saturated sample method. Data collection methods using interviews and questionnaires using a Likert scale, as well as distributing questionnaires using Google Form. The data analysis technique used is Path Analysis (Structural Equation Modeling-Partial Least Square (SEM PLS) using inner models and outer models and simultaneously with validity and reliability tests. The results of the research show that 1) Organizational culture has a positive and significant effect on satisfaction Work; 2) Job satisfaction has a positive and significant effect on employee performance; 4) Organizational culture has no effect on employee performance; 5) Organizational culture has a positive and significant effect on employee performance through job satisfaction.